2019
DOI: 10.1108/k-06-2019-0430
|View full text |Cite
|
Sign up to set email alerts
|

An improved hybrid particle swarm optimization for multi-objective flexible job-shop scheduling problem

Abstract: Purpose With the continuous upgrading of the production mode of the manufacturing system, the characteristics of multi-variety, small batch and mixed fluidization are presented, and the production environment becomes more and more complex. To improve the efficiency of solving multi-objective flexible job shop scheduling problem (FJSP), an improved hybrid particle swarm optimization algorithm (IH-PSO) is proposed. Design/methodology/approach After reviewing literatures on FJSP, an IH-PSO algorithm for solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Palacio et al [43] proposed a GA hybridized with TS and heuristic seeding to minimize the total time needed to complete all jobs, thereby increasing the feasibility and connectivity of their algorithms. Zhang et al [53] developed a hybrid algorithm that combined PSO with GA and SA. This algorithm was designed to utilize the fast convergence speed of the traditional PSO algorithm, which inherits excellent genes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Palacio et al [43] proposed a GA hybridized with TS and heuristic seeding to minimize the total time needed to complete all jobs, thereby increasing the feasibility and connectivity of their algorithms. Zhang et al [53] developed a hybrid algorithm that combined PSO with GA and SA. This algorithm was designed to utilize the fast convergence speed of the traditional PSO algorithm, which inherits excellent genes.…”
Section: Methodsmentioning
confidence: 99%
“…The job sequence represents the job allocation inside the machines. Allocation problems that combine resource and job sequences are typical in JS-FMS planning and scheduling [20,21,24,31,32,36,40,42,46,48,50,53,56,57,59,62]; this is because the workflow of a job shop is unidirectional or recursive, as there are no constraints on the machines that perform only the first operation of a job or the last operation of the job [8]. Meanwhile, the product sequence concentrates on the sequence of products when a specific product enters a machine.…”
Section: Sequence Typementioning
confidence: 99%
See 2 more Smart Citations
“…Dabah et al [40] paralleled the tabu search algorithm to solve the blocking job shop scheduling problem and used data in the existing literature to verify that the designed algorithm can improve upon the best results achieved by a large number of benchmark methods in the literature. Zhang et al [41] proposed an improved hybrid particle swarm optimization algorithm to study the multiobjective flexible job shop scheduling problem. e benchmark experiment showed that the algorithm has the advantages of high quality and fast convergence.…”
Section: Literature Reviewmentioning
confidence: 99%